2011
DOI: 10.1093/ntr/ntq236
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic Efficacy for Smoking Cessation: Preliminary Assessment of a New Instrument

Abstract: Introduction: Smoking cessation research has demonstrated a link between social support and quitting, but interventions designed to enhance partner support have often failed. We adapted and tested a measure of dyadic efficacy to assess smokers' confidence in their abilities to work together as a team with their partners to quit smoking and cope with quitting challenges. Our goal was to establish the psychometric properties of the dyadic efficacy instrument, including its associations with cessation outcomes. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 26 publications
3
37
0
Order By: Relevance
“…Our prior work (17) suggests a relationship between dyadic efficacy and smoking cessation. Dyadic efficacy was introduced with the following: “Think about the ONE person in your life who you consider to be your main source of support.…”
Section: Methodsmentioning
confidence: 90%
“…Our prior work (17) suggests a relationship between dyadic efficacy and smoking cessation. Dyadic efficacy was introduced with the following: “Think about the ONE person in your life who you consider to be your main source of support.…”
Section: Methodsmentioning
confidence: 90%
“…Studies that proactively involve social networks in smoking cessation have mainly centred on the general adult population 182 and remain under-researched in pregnancy. Only five such studies were identified in the most recent Cochrane review 183 of psychosocial interventions to support women to stop smoking in pregnancy.…”
Section: Valentementioning
confidence: 99%
“…In a recent longitudinal study of couples in which one or both partners smoked, higher perceived partner responsiveness at baseline predicted a decreased likelihood of smoking and fewer cigarettes smoked per day nine years later (Derrick, Leonard, & Homish, 2013). Smokers who are confident in their ability to work with their partner as a team in a smoking cessation effort are more likely to successfully quit (Sterba, et al, 2011), and there is evidence that partners of smokers are interested in helping their partners quit (Thomas, et al, 2009). Positive partner support for quitting smoking has been related to higher engagement in smoking cessation treatment (Richardson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%